Aspectos penales y características clínicas de la criminalidad en la esquizofrenia - Josune Tejero (Salud Mental, 2002)
As a general rule, people are held responsible for their behavior.Nevertheless, some are not judged as criminals by justice, onbehalf of their mental condition.The present work offers a review of the penitentiary frame forpeople with mental illness who have commited a crime, and pointsout the relationship between schizophrenia, aggression andcriminality.In Mexico, a person who commits a crime is sanctioned orpunished by the State and to do that, it is necessary to prove thesubjects guilt.If a person lacks the maturity and necessary mental faculties torecognize the crime committed, culpability isnt present and thesubject is considered inimputable. This is a cause for crimeresponsibility exclusion, and a most important feature regardingpeople with mental disorders.In spite that criminal responsibility is associated with conceptssuch as free will or free choice, in practice it is related to imputabilityor inimputability...